Investigating Heritage Language Processing: Meaning Composition in Chinese Classifier-Noun Phrasal Contexts - Li, Fei; Hong, Xiangfei; He, Zhaoying; Wu, Sixuan; Zhang, Chenyi (Frontiers in Psychology, 2021)
The aim of the present study was to investigate how Chinese-Malay bilingual speakers with Chinese as heritage language process semantic congruency effects in Chinese and how their brain activities compare to those of monolingual Chinese speakers using electroencephalography (EEG) recordings. To this end, semantic congruencies were manipulated in Chinese classifier-noun phrases, resulting in four conditions: (i) a strongly constraining/high-cloze, plausible (SP) condition, (ii) a weakly constraining/low-cloze, plausible (WP) condition, (iii) a strongly constraining/implausible (SI) condition, and (iv) a weakly constraining/implausible (WI) condition. The analysis of EEG data focused on two event-related potential components, i.e., the N400, which is known for its sensitivity to semantic fit of a target word to its context, and a post-N400 late positive complex (LPC), which is linked to semantic integration after prediction violations and retrospective, evaluative processes. We found similar N400/LPC effects in response to the manipulations of semantic congruency in the mono- and bilingual groups, with a gradient N400 pattern (WI/SI>WP>SP), a larger frontal LPC in response to WP compared to SP, SI, and WI, as well as larger centro-parietal LPCs in response to WP compared to SI and WI, and a larger centro-parietal LPC for SP compared to SI. These results suggest that, in terms of ERP data, Chinese-Malay early bilingual speakers predict and integrate upcoming semantic information in Chinese classifier-noun phrase to the same extent as monolingual Chinese speakers. However, the global field power (GFP) data showed significant differences between SP and WP in the N400 and LPC time windows in bilinguals, whereas no such effects were observed in monolinguals. This finding was interpreted as showing that bilinguals differ from their monolingual peers in terms of global field power intensity of the brain by processing plausible classifier-noun pairs with different congruency effects.